Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T15:31:01+02:00
P = d/m RT , m
P = d/m RT | *m
P *m =dRT | :p
m = dRT

f = 9/5 c + 32 | *5
5f = 9c + 32 | -32
5f + 32 = 9c

s = vt + at²/2 | *2
2s = 2vt + at² | -2vt
2s - 2vt = at² | : t²
(2s - 2vt) : t² = a

F = G Mm/r² | *r²
F * r² = G* Mm | :GM
( F * r²) :GM = m
Chyba tak
2010-04-14T15:32:39+02:00
A) P = d/M RT ; M
MRTP=d
M=d/(RTP)

b) f = ⁹/₅c + 32 ;c
⁹/₅c =f-32
9c=5(f-32)
c=(5(f-32))/9

c) s= vt + at²/2 ;a
2s=vt+at²
at²=2s-vt
a=(2s-vt)/t²

d) F = G Mm/r² ;m
Fr² =GMm
m=(Fr²)/(GM)